Characteristics of vascular endothelium in young patients with epilepsy - A. I. Fedin; E. V. Starykh; O. A. Baranova; A. V. Chekanov; D. V. Torshin (Эпилепсия и пароксизмальные состояния, 2018)
The objective was to study the state of vascular walls in young patients at various stages and various courses of epilepsy.Materialsand methods. We examined 62 patients of young age with focal symptomatic and cryptogenic epilepsy for hanges in their blood vessels. Photoplethysmography combined with a non-invasive diagnostic system (“Angioscan Electronics”, Russia) were used. The patients were divided into 3 groups: 1) patients after a single (first) epileptic seizure; 2) patients with remission; 3) patients with treatment-resistant seizures.Results. We found no structural changes in their blood vessels. However, the occlusion test showed changes in the functional state of large muscle arteries in all groups of epileptic patients. In addition, changes in microcirculatory beds were detected in patients after a single seizure and in those resistant to treatment. Patients after single epileptic seizures showed the largest changes in small resistance arteries and arterioles.Conclusion. The results suggest that functional characteristics of vascular endothelium change in young patients suffering from epilepsy.